Pemanfaatan Teknologi Augmented Reality Sebagai Media Navigasi Berbasis Aplikasi Android - Ganda Sinarna; Enny Itje Sela (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The navigation media on the Universitas Teknologi Yogyakarta campus environment currently still uses conventional guidance media in the form of printed pictures and mock-up plans, so it is considered ineffective and inefficient in providing directions for students, staff, or campus visitors, especially in the outdoor areas where signage is rarely installed. This research aims to assist 3D virtual navigation services by utilizing augmented reality technology based on longitude and latitude coordinate point data of an area, which is implemented in the form of an Android mobile application. The research method used is the case study method, with a qualitative approach. This application development model uses the waterfall model. The stages used in this research include planning, data collection, analysis, design, implementation, and application testing using Black box testing with the test case method, which produces application testing that descriptively explains the application work process. Application test results show that route search navigation, information features, and application menus work well. The combination of augmented reality technology and a global positioning system can be implemented to recognize various navigation routes based on longitude and latitude numerical values very well.